Evaluation of the association between right ventricular lead placement and future need for upgrade from pacemaker or ICD to cardiac resynchronization therapy. A population-based comparative study. (3rd October 2022) - Borgquist, R; Farouq, M; Sonesson, L; Safstrom, K; Platonov, P G
Abstract: Background: Between 10–20% of patients who are implanted with a pacemaker due to AV block, are diagnosed with heart failure within two years post-implant. It has been suggested that septal placement of the right ventricular lead is associated with lower risk of heart failure for patients who receive ventricular pacing. However, randomized trials and registry studies have yielded conflicting data on this topic. We therefore sought to use a nationwide pacemaker-registry to investigate whether septal lead placement at primary pacemaker implantation due to bradycardia is associated with lower risk of need for upgrade to cardiac resynchronization therapy (CRT). Purpose: To investigate the association between right ventricular lead placement and risk of future upgrade to CRT, either within two years or later during follow-up. Methods: The rates of CRT upgrades were compared between patients who received their pacemaker implants at two tertiary care centers who implant pacemakers and perform all CRT implantations in their respective regional uptake areas. One center consistently used septal RV lead placement for all implants, while the other used apical lead placement. CRT indications were guideline-based and did not differ between sites. Data from the national pacemaker-registry was extracted for all patients and compared between the sites. Pacemaker indications with presumed high ventricular pacing need were defined as AV block II/III or chronic atrial fibrillation with bradycardia. Results: 15809 patients with either pacemaker (n=14258) or implantable cardioverter defibrillator (ICD, n=1553) were included and followed for a median of 9 years. Mean age at implant was 75±13 years and 40% were female (see table 1 for demographic details). A total of 358 CRT upgrades (2.3%) were performed, of which 91 (25%) occurred within two years of the primary implant. Univariate and multivariate logistic regression analysis results are presented in table 2. Independent predictors of CRT upgrade included apical lead placement (odds ratio 1.4 [95% CI 1.0–1.7], p=0.02 and presumed high ventricular pacing need (AV block or chronic atrial fibrillation, OR 1.6 [1.2–2.0] p<0.001). In a prespecified sub-analysis for CRT upgrade within two years post-implant, the OR for apical lead placement was similar (1.5 [0.9–2.6]) but non-significant (p=0.14). Conclusions: In pacemaker therapy, apical RV lead placement (compared to septal lead placement) was associated with higher risk for CRT upgrade. Other factors such as gender and high likelihood of ventricular pacing need were also associated to CRT upgrades. In general, upgrade to CRT was relatively uncommon in this large population-based material, perhaps indicating an undertreatment with CRT for pacemaker-induced cardiomyopathy. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Heart and Lung FoundationALF governmental grant within the Swedish healthcare system